PERAN PENDIDIKAN ISLAM DALAM MENGHADAPI UJIAN COVID 19 (Studi Kritis Adanya Pendemi Covid 19) - Mihmidaty Ya’cub (CENDEKIA: Jurnal Studi Keislaman, 2020)
God is the educator of all human beings in this universe. In the process of educating this human being, God also gave human beings a test. The test that God sent down on human beings on this earth is due to human behavior that tends to deviate from religion, is inconsistent with its recognition as a believer, does not prioritize obedience to God, so God tests in the form of fear, hunger, lack of wealth, soul and fruit- fruit. God's test in general, revealed to all human beings. The attitude of facing the test taught by God is Back to God, many dhikr to God to calm the heart, believing that all tests, come from God and nothing is useless there must be wisdom behind it, be patient and only complain about his troubles to God. Islamic education in the face of this Corona virus pandemic, in formal educational institutions, among others, increase the application of learning methods and strategies that link subject matter to real life through online learning, add clear and reassuring learning material, delivered by professional teachers. And in non-formal institutions is to increase the role of the mosque for worship and guidance of the ummah by referring to health protocols. Activating Majelis ta'lim through online studies, optimizing social media with Islamic content and following bai'at thariqah. The wisdom of the Corona virus test, among others, is to get closer to God, repent, high social solidarity, clean lifestyle, healthy eating pattern, prioritize peace of mind, Sakinah family, exalted by God, granted prayers and melted by God for more obedience to Him.